Efeito da fotobiomodulação sobre células musculares cultivadas com meio condicionado de macrófagos ativados para perfil M1 - Santos, Tainá Caroline dos (2019)
Due to their functional role, skeletal muscles represent the most common organ susceptible to injuries. However, this tissue has a high adaptive and regenerative capacity due to the presence of satellite muscle cells (SC) that, after an acute injury, are able to activate, proliferate, differentiate and fuse to reconstitute the área that is injurie. The macrophages have a great influence and importance to the skeletal muscle regeneration process, since the products secreted by them can influence the different stages of muscle repair. Photobiomodulation (PBM) has been demonstrated in the literature, positive effects in the process of muscle repair in the modulation of migration and cell proliferation viability, such as the synthesis of inflammatory mediators in different cell lines of macrophages and myoblasts. In the present study, the aim was to evaluate the effects of PBM in cell viability, proliferation and differentiation and synthesis of nitric oxide (NO), IL- 6 and TNF-α on satellite muscle cells (C2C12) in undifferentiated and differentiated stages cultivated in a presence of activated M1 (LPS and IFN-Ɣ) J774 macrophages profile conditioned medium irradiated with same dosimetric parameters. The groups were evaluated under the experimental conditions: (A) proliferation C2C12 myoblasts condition (10% Fetal Bovine Serum - FBS): (1) C2C12 NI (non-irradiated) + proliferation medium, (2) C2C12 NI + non-activated macrophage conditioned medium (MM), (3) C2C12 NI + M1 MM non-irradiated, (4) C2C12- PBM+ M1 MM non-irradiated, (5) C2C12 NI + M1 MM irradiated, (6) C2C12-PBM + M1 MM irradiated; and (B) myoblasts C2C12 in differentiation condition (2% Horse Serum – HS): (7) C2C12 NI (non-irradiated) + differentiation medium, (8) C2C12 NI + non-activated MM, (9) C2C12 NI + M1 MM non- irradiated, (10) C2C12- PBM+ M1 MM non-irradiated, (11) C2C12 NI + M1 MM irradiated, (12) C2C12-PBM + M1 MM irradiated. ). The irradiation was performed once using an aluminum-gallium-arsenide (780 nm, 70 mW, 17,5 J/cm2, 1 J). Myoblasts C2C12 were cultivated in proliferation medium (10% FBS) and a differentiation medium process were induced by replacing the proliferation medium to differentiation medium (2% HS – 72h), they were irradiated, seeded in plates and received 30 and 50% (v/v) of macrophage conditioned-medium and cells were incubated at 370C, 5% CO2 for 24 and 48h. At the end of this period the cell viability, proliferation and the NO synthesis were assessed using MTT, Crystal Violet and Griess method respectively and IL-6 and TNF-α synthesis were assessed using ELISA. Myoblasts differentiation was evaluated by nuclear distribution and fusion index May-Grunwald and Giemsa staining. Three independent experiments were performed. All results were analyzed statistically. The cells treated with PBM showed positive effects as regards in enhance of cell viability and proliferation of undifferentiated SC after 48h cultivated in a higher concentration (50%) of M1 conditioned medium irradiated and enhance in C2C12 differentiated viability (48h) cultivated in both concentrations and enhance proliferation (48h) when cultivated in lower concentration (30%) of M1 macrophage conditioned medium irradiated. Decreased NO synthesis of irradiated SC in proliferation and differentiation stages when was cultivated in both concentrations of M1 macrophages conditioned medium after 24 and 48h. At protein level, showed a pro-inflammatory cytokines decreased when cultivated in both concentrations, such as: IL-6 decreased in undifferentiated SC treated with PBM after 24 and 48h and TNF-α decreased after 48h of undifferentiated and differentiated SC. And PBM showed an advantage of differentiation process (index fusion) of undifferentiated SC (24 and 48h) and differentiated SC (48h) when cultivated in both concentrations of M1 macrophages conditioned médium irradiated. In conclusion, the PBM can generate positive effects in satellite muscle cells cultivated in a microenvironmetal with differents concentrations of products secreted by pro-inflammatory (M1) macrophages also irradiated with same dosimetric parameters, in relation to decrease in NO syntesis and inflammatory citokines and in the advantage of differentiation process of satellite muscle cells (fusion index).